Characterisation of homologous recombination deficiency in paired primary and recurrent high-grade serous ovarian cancer. Issue 9 (30th October 2018) - Patel, Jai; Braicu, Ioana; Timms, Kirsten; Solimeno, Cara; Tshiaba, Placede; Reid, Julia; Lanchbury, Jerry; Darb-Esfahani, Silvia; Ganapathi, Mahrukh; Sehouli, Jalid; Ganapathi, Ram
Abstract Background Homologous recombination deficiency (HRD) is shown to predict response to DNA-damaging therapies in patients with high-grade serous ovarian cancer (HGSOC); however, changes in HRD during progression remains unknown. Methods HRD scores were evaluated in paired primary and/or recurrent HGSOC samples (N  = 107) from 54 patients with adjuvant platinum-based chemotherapy.BRCA1/2 mutation, BRCA1 methylation, loss of heterozygosity (LOH), and HRD scores were characterised using tumour DNA-based next-generation sequencing assays. Results Among 50 evaluable pairs (N  = 100 samples), high intra-patient correlation in HRD score was observed (r 2  = 0.93).BRCA1/2 mutations, BRCA1/2 LOH, and HRD were maintained between primary and recurrent samples, except for one pair in which aBRCA1 reversion mutation was identified in the recurrent sample. Despite the reversion, both samples were classified as having high HRD scores ( ≥ 42). All samples withBRCA1 /2 mutations exhibited high HRD scores; however, high HRD scores were more prevalent thanBRCA1 /2 mutations (55% vs. 30%, respectively). Conclusion Markers of HRD were maintained between the primary and recurrent samples, regardless of other genomic changes that occurred during recurrence. HRD score/markers in primary tumours may be valuable and adequate for selection of platinum-based therapy and/or poly-ADP-ribose-polymerase (PARP) inhibitors in recurrent HGSOC.